2014
DOI: 10.1371/journal.pone.0099031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Domain-Specific Noise on Visual Motion Processing in Schizophrenia

Abstract: BackgroundVisual perception impairments in schizophrenia stem from abnormal information processing. Information processing requires neural response to a stimulus (signal) against a backdrop of 1) random variation in baseline neural activity (internal noise) and sometimes irrelevant environmental stimulation (external noise). Filtering out noise is a critical aspect of information processing, and needs to be critically examined in schizophrenia.MethodsTo understand how noise in the visual system constrains perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Slaghuis et al (2007) found coherent motion deficits in schizophrenia patients for lower but not higher velocities. Chen et al (2014) found speed discrimination deficits when the target had only low or moderate amounts of speed noise. Kim, Park and Lee (2005) suggest that patients may primarily be more prone to falsely recognizing biological motion when discriminating intact and phase-scrambled point-like walkers (see also Task 3 of Kim et al, 2013).…”
Section: 0 Discussionmentioning
confidence: 93%
“…Slaghuis et al (2007) found coherent motion deficits in schizophrenia patients for lower but not higher velocities. Chen et al (2014) found speed discrimination deficits when the target had only low or moderate amounts of speed noise. Kim, Park and Lee (2005) suggest that patients may primarily be more prone to falsely recognizing biological motion when discriminating intact and phase-scrambled point-like walkers (see also Task 3 of Kim et al, 2013).…”
Section: 0 Discussionmentioning
confidence: 93%
“…The presence of external noise did interfere with non-face visual processing in schizophrenia patients (Chen et al, 2014; Kim et al, 2013; Chen et al, 2008; Chen et al, 2003; Stuve et al, 1997). While this study showed quantitative differences between the noise effects in face processing and in non-face visual processing, whether qualitative differences exist in schizophrenia remains unclear.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have been focused on how different functional domains such as affective and non-affective processing of facial images are altered in schizophrenia patients (Heimberg et al, 1992; Gur et al, 2002; Butler et al, 2008; Chen et al, 2009; Chen et al, 2008; Silverstein et al, 2009; McBain et al, 2010; Lee et al, 2011; Yoon et al, 2006; Lee et al, 2007). Noise-filtering is essential for the processing of perceptual information including faces, and appears to be implicated in various aspects of deficient perceptual processing in schizophrenia (Chen et al, 2014; Kim et al, 2013; Chen et al, 2008). A recent study proposed heightened noise levels as a mechanism underlying abnormal facial processing in schizophrenia (Spencer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings at high temporal frequencies might also reflect increased internal noise (decreased signal-noise ratios) in those who exhibited high schizotypy scores. In the context of schizophrenia, a recent study (Chen et al 2014) using random dot kinematograms has shown that schizophrenics exhibited significantly poorer speed discrimination across a range of speeds (5.25-13.0 deg/s) and their performance was more susceptible to the addition of noise compared to controls.…”
Section: Discussionmentioning
confidence: 99%